2005
DOI: 10.1002/micr.20122
|View full text |Cite
|
Sign up to set email alerts
|

Addition of nitric oxide donor S-nitroso-N-acetylcysteine to selective iNOS inhibitor 1400W further improves contractile function in reperfused skeletal muscle

Abstract: This study examines the effects of combination therapy with the nitric oxide (NO) donor S-nitroso-N-acetylcysteine (SNAC) and the iNOS inhibitor N-(3-(aminomethyl)benzyl) acetamidine (1400W) on contractile function in reperfused rat skeletal muscle. The right extensor digitorum longus (EDL) muscles of 104 rats were subjected to 3 h of ischemia followed by reperfusion times of 3 h, 24 h, and 7 days. For each time period, rats were further divided into sham operation, control, 1400W only, and 1400W plus SNAC gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…The increase in iNOS activity in the present study is clearly time-dependent, which complies with the finding that iNOS protein and catalytic activity were detectable in rat brain 12 h after cerebral ischaemia, with the peak at 48 h and return to the baseline at 168 h [18]. iNOS up-regulation by pro-inflammatory cytokines is directly associated with I/R injury in a wide variety of tissues including bladder [4], skeletal muscle [19], kidney [20], brain [21], etc. A high level of NO derived from iNOS has been reported to react with superoxide generated during reperfusion, and generate the highly toxic peroxynitrite anion, leading to tissue injury with further cytokine and inflammatory mediator production.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The increase in iNOS activity in the present study is clearly time-dependent, which complies with the finding that iNOS protein and catalytic activity were detectable in rat brain 12 h after cerebral ischaemia, with the peak at 48 h and return to the baseline at 168 h [18]. iNOS up-regulation by pro-inflammatory cytokines is directly associated with I/R injury in a wide variety of tissues including bladder [4], skeletal muscle [19], kidney [20], brain [21], etc. A high level of NO derived from iNOS has been reported to react with superoxide generated during reperfusion, and generate the highly toxic peroxynitrite anion, leading to tissue injury with further cytokine and inflammatory mediator production.…”
Section: Discussionsupporting
confidence: 90%
“…The above possible mechanism for the induction of iNOS is a positive feedback loop [19]. Recently, treatment with 1400W as an iNOS inhibitor has been reported to ameliorate I/R injury [19–21]. In the present study, 1400W significantly suppressed the increase in iNOS enzymatic activity after I/R but failed to affect the cNOS activity, suggesting that 1400W at this dose acts as an iNOS‐selective inhibitor.…”
Section: Discussionmentioning
confidence: 40%
“…Previous studies by others showed that by using variety types of treatments, muscle injury caused by 3 h TK could be reduced at acute time points of 1, 2, 3, 4, 24, 48 h, and 7 d [9,[33][34][35][36][37][38][39][40][41]. However, there is a lack of a study showing beneficial effects of any treatment that lasts for a longer time period.…”
Section: Discussionmentioning
confidence: 87%
“…Traditionally, rubber band tourniquets and vascular clips have been used to induce ischemia in mouse hindlimb. 3,7,9,10,23,25 However, both methods have certain disadvantages. Rubber bands may induce crushing injury to the tissue due to the high local compression, 5 and vascular clips require surgeries which may induce more variability and complications.…”
Section: Discussionmentioning
confidence: 97%